2020
DOI: 10.3389/fpsyg.2020.00662
|View full text |Cite
|
Sign up to set email alerts
|

Imitation in Chinese Preschool Children: Influence of Prior Self-Experience and Pedagogical Cues on the Imitation of Novel Acts in a Non-Western Culture

Abstract: Both prior experience and pedagogical cues modulate Western children's imitation. However, these factors have not been systematically explored together within a single study. This paper explored how these factors individually and together influence imitation using 4-year-old children born and reared in mainland China (N = 210)-a country that contains almost one-fifth of the world's population, and in which childhood imitation is under-studied using experimental methodology. The behavior of children in this cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…For example, in Clegg and Legare (2016), children replicated irrelevant actions as part of making a bead necklace (e.g., using each bead to touch the forehead before stringing it on the necklace) only when the task was coupled with normative framing (e.g., the statement that ‘everyone here always does this’). Similarly, it has been reported that children tend not to over‐imitate when the demonstrator is a puppet (McGuigan & Robertson, 2015), when the demonstrator is absent (Nielsen & Blank, 2011), when a more efficient approach has been shown to them (Schleihauf, Pauen, & Hoehl, 2019), when the efficient approach has been experienced through prior self‐action (Wang & Meltzoff, 2020; Williamson & Meltzoff, 2011), or even when the demonstrator has previously displayed anti‐social behaviours (Wilks, Kirby, & Nielsen, 2019). Indeed, children’s decision about whether to imitate causally irrelevant acts in a high‐fidelity manner (over‐imitation) versus directly achieving the causal outcome in an efficient way is now thought to be context dependent, and governed at least in part, by cues that inform the child to attend to social conventions (Krieger, Aschersleben, Sommerfeld, & Buttelmann, 2020; Legare, Wen, Herrmann, & Whitehouse, 2015).…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…For example, in Clegg and Legare (2016), children replicated irrelevant actions as part of making a bead necklace (e.g., using each bead to touch the forehead before stringing it on the necklace) only when the task was coupled with normative framing (e.g., the statement that ‘everyone here always does this’). Similarly, it has been reported that children tend not to over‐imitate when the demonstrator is a puppet (McGuigan & Robertson, 2015), when the demonstrator is absent (Nielsen & Blank, 2011), when a more efficient approach has been shown to them (Schleihauf, Pauen, & Hoehl, 2019), when the efficient approach has been experienced through prior self‐action (Wang & Meltzoff, 2020; Williamson & Meltzoff, 2011), or even when the demonstrator has previously displayed anti‐social behaviours (Wilks, Kirby, & Nielsen, 2019). Indeed, children’s decision about whether to imitate causally irrelevant acts in a high‐fidelity manner (over‐imitation) versus directly achieving the causal outcome in an efficient way is now thought to be context dependent, and governed at least in part, by cues that inform the child to attend to social conventions (Krieger, Aschersleben, Sommerfeld, & Buttelmann, 2020; Legare, Wen, Herrmann, & Whitehouse, 2015).…”
Section: Introductionmentioning
confidence: 82%
“…This addressed recent calls in psychology (Rad et al, 2018), and developmental psychology in particular (Nielsen, Haun, Kärtner, & Legare, 2017), that researchers should strive to gather data from a broader range of cultures than the Western ones, which have been used in the majority of published studies. We chose to test pre‐schoolers from China, a traditional, east‐Asian Chinese culture which contains almost one‐fifth of the world’s population – and this broadens our knowledge about children’s imitation within a country in which children’s social behaviour has rarely been studied using experimental methods (for exceptions see, Li, Liao, Cheng, & He, 2019; Wang & Meltzoff, 2020; Wang, Williamson, & Meltzoff, 2015; Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps this is because the university teachers are in an environment or social relations full of competing interests, hence, further validation is required in the future. The psychology of research conformity is studied in the context of traditional Chinese culture, and some studies have shown that Chinese researchers are more emotionally motivated to be compliant [ 58 ]. Finally, the qualitative study mainly used in-depth interviews with the aim of analyzing the types and motivational characteristics of SRC, but there are limitations, as the unstructured nature of the survey makes the results very susceptible to the interviewer’s own influence, and the integrity of the quality of the results is very dependent on the interviewer’s skill, which may lead to one-sided or superficial information obtained in the study.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%